‘Forgiving’ in Derrida’s philosophy of meeting, or on ethics as an function of language - Podstawski, Michał (Hybris, 2013)
Ethics, which became a central point of the late works by Jacques Derrida, is a peculiar project within works of this scholar. Even an observation that the ‘deconstruction’ was solely an initial epistemological procedure, whose aim was to force its way through tissue of appropriating discourses, in order to make it available for ethics to exist from the beginning, once again, does not exhaust the risen issue. Ethics, as interpreted by Derrida, is based on the categories of the philosophy of meeting – first of all in the Levinas’ version – but is in no way exhausted within its classical interpretations. A reason for such a situation is a high status given to a language by the author of the ‘Margins of Philosophy’. The philosophy of meeting, according to him, takes place in words, gestures and events, which dialoging is an introduction to construction of a fundamental ethic situation, i.e. the moment of meeting. One of such  keywords is ‘forgiving’ – that becomes not only a signal of openness to accept the other, but also a communicative slogan, creating a horizon of ethics. It turns out that an ability of ‘forgiving’ is a basic condition. Through meeting it we can give each other a hand, and overcome the surrounding walls and entanglements. This is the feature of ‘forgiving’, where Derrida sees a basic chance for survival of the most precious values of our culture.